Peningkatan Prinsip Governance dalam Perencanaan Pelayanan Administrasi Kependudukan (Studi pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Pasangkayu) - Samang, Andi Idil Sangiang (Jurnal Ilmiah Administrasi Publik, 2021)
This study aims to describe and analyze: (1) administrative service planning and (2) alternative service planning in improving. The results showed that in terms of the planning process, as a whole that Dinas Kependudukan Dan Pencatatan Sipil had not fully carried out the planning optimally, this was seen from not involving the community as the main party users of services besides that in the formulation it did not involve all stakeholders in every stage carried out. In order to improve governance in Dinas Kependudukan Dan Pencatatan Sipil services, then a service planning concept is compiled that incorporates governance principles and of course is supported by good population administration arrangements and adequate support capacity as well. The alternative services provided are population administration service planning at Dinas Kependudukan Dan Pencatatan Sipil based on the principles of good governance. In addition, service planning should be able to improve the existence of good governance by involving stakeholders, not only the government but also the public and the private sector.